1995
DOI: 10.1111/j.1365-2265.1995.tb02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sporadic medullary thyroid carcinoma: the importance of routine measurement of serum calcitonin in the diagnostic evaluation of thyroid nodules

Abstract: This study demonstrates a surprisingly high prevalence of sporadic forms of medullary thyroid carcinoma in patients with nodular thyroid disease. Such forms of medullary thyroid carcinoma seem to be unrelated to iodine intake and may be pure or mixed with a follicular carcinoma. In these mixed thyroid carcinomas, only the neoplastic follicular pattern was seen on both cytological and histological examination. Routine measurements of serum calcitonin levels should therefore be considered an integral part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
2
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 29 publications
7
77
2
11
Order By: Relevance
“…The prevalence of hypercalcitoninemia not due to MTC varies from 0.3 to 4.5% (2)(3)(4)(5)(6)(7)(8)(9). The assay's high cost and lack of specificity (25) has dissuaded health authorities in the USA from adopting systematic testing (1,26).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of hypercalcitoninemia not due to MTC varies from 0.3 to 4.5% (2)(3)(4)(5)(6)(7)(8)(9). The assay's high cost and lack of specificity (25) has dissuaded health authorities in the USA from adopting systematic testing (1,26).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in 5-10% of thyroid tumors (1) and has a prevalence of between 0.3 and 1.37% in nodular thyroid disease (2)(3)(4)(5)(6)(7)(8)(9). Calcitonin (C T ) is a marker for both initial diagnosis and monitoring of patients with residual or recurrent MTC (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, two diagnostic tools are available for the evaluation of patients with NTD, including those with MTC: FNAC and measurement of human C t concentrations. Previous European studies recruiting large series of patients with NTD (6)(7)(8)(9)(10)(11)(12) demonstrated that it is possible to diagnose MTC earlier with C t screening than FNAC, particularly in patients with nodules smaller than 10 mm (microMTCs). Hence, the ETA has recommended C t screening in all subjects with NTD (13).…”
Section: The Thyroid Isthmus and The Parafollicular C Cellsmentioning
confidence: 99%
“…Several studies (6)(7)(8)(9)(10)(11)(12) on sporadic MTC have demonstrated that the earlier the diagnosis the better the prognosis of MTC. C t has been shown to represent a sensitive marker for MTC, leading to the early diagnosis of the neoplasm even when fine needle aspiration cytology (FNAC) discloses benign features (as occurs in nodules smaller than 10 mm).…”
Section: Introductionmentioning
confidence: 99%